PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP KEMAMPUAN HOTS MATEMATIKA SISWA KELAS IV SD NEGERI 72 PALEMBANG - Rika Pebyola Simanjuntak; Misdalina; Ferri Hidayad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Think Pair Share (TPS) learning modelon the Higher Order Thinking Skills (HOTS) in mathematics of fourth-grade studentsat SD Negeri 72 Palembang. This research employed a quantitative method with atrue experimental design, specifically the Posttest-Only Control Group Design. Thepopulation consisted of all fourth-grade students, with a sample of 55 studentsselected using cluster random sampling, divided into an experimental class (27students) and a control class (28 students). Data were collected through a HOTS-based mathematics test consisting of essay questions. Prerequisite tests includednormality (Shapiro-Wilk) and homogeneity (Levene’s Test). The hypothesis wastested using an independent sample t-test. The results showed that the averagescore of the experimental class was 80.19, significantly higher than the control classwhich averaged 21.25. The t-test results indicated a significance value (2-tailed) of0.000 < 0.025, leading to the rejection of H0 and acceptance of Ha. Thus, it can beconcluded that the Think Pair Share learning model has a significant positive effecton the mathematical HOTS abilities of fourth-grade students at SD Negeri 72Palembang.